The opinion of Sheikh Al-Shaarawi (T.: 1419 AH) on the suspicions raised about the custody of men over women - Younes, Nour; Shehab , Mohamed (Islamic Sciences Journal, 2023)
Women’s issues are among the most controversial issues in the intellectual and political milieu in the Arab world, and among these issues is the issue of men’s guardianship over women. The guardianship of family affairs granted by Islam to men is one of God’s blessings on humans, as it is appropriate for both men and women. This is because of the traits that both genders are endowed with, and also because of the innate predispositions they have. This is what the enemies of Islam did not understand, so they tried to distort the Islamic religion by casting doubts on it in direct or indirect ways, misleading the woman that they were sympathetic to her and pity her matter. But they bury her torment, all because of their lack of understanding of the meaning of guardianship and its legal controls, and our distinguished scholars have ensured the response to Such suspicions, including Sheikh Muhammad Metwally Al-Shaarawi, "may God have mercy on him", who wrote many books related to women, and the researcher mentioned his opinion on this suspicion in detail in this research, and I also included some statements of Muslim thinkers. This study also mentioned the sayings of some Westerners regarding Islam’s honoring of women in this stewardship. So that at the conclusion of the research we will invalidate the statements of the secularists regarding this suspicion, and that Islamic law honors women and raises their status with this stature. This research has been organized into three sections.